A snapshot of a pathogenic bacterium mid-evolution: Neisseria meningitidis is becoming a nitric oxide-tolerant aerobe. (21st November 2011) - Moir, James W.
Abstract : Members of the Neisseria genus typically display the ability to carry out denitrification of nitrite to nitrous oxide as an alternative to oxygen respiration when oxygen is depleted. The key enzymes nitrite and nitric oxide reductase are found across the Neisseria genus. Within Neisseria meningitidis, however, a number of research groups have found that a significant proportion of strains lack a functional nitrite reductase. It appears that N. meningitidis is on an evolutionary trajectory towards loss of the capacity to reduce nitrite. In the present paper, I propose that N. meningitidis is evolving to become a nitric oxide-tolerant aerobe in order to occupy an oxygen-rich niche close to host tissue (and hence oxygen perfusion). Other features of the genomic and functional specialization of N. meningitidis, such as possession of a polysaccharide capsule and various acquired reactive oxygen species-resistance mechanisms, support this proposition. The importance of oxygen availability more generally is discussed with reference to recent findings with other mucosal pathogens.